2015
DOI: 10.4236/gsc.2015.54019
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile and Physico-Chemical Parameters of Castor Oils in Tanzania

Abstract: This paper reports on the assessment of the quality and quantity of castor oil from castor seeds collected from different regions in Tanzania. The castor seeds from Arusha, Dar es Salaam, Dodoma, Iringa, Kagera and Morogoro regions in Tanzania were extracted by Soxhlet method using n-hexane and the oil yields were determined. The yields were 52.78%,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 6 publications
10
68
2
2
Order By: Relevance
“…For instance, cold-pressed castor oils have low acid value, low iodine value and a slightly higher saponification value than solvent-extracted oil [1]. It has further been observed that castor seeds from different climatic conditions produce castor oils of different composition and physical-chemical properties [14,15,17]. Malaysian castor seeds for instance, contain total lipids (castor oil) reaching up to 43.3 % per dry weight and a saponification value of 182.96 mg KOH/g [14] while for the Nigerian castor seeds, the total lipids (castor oil) is 48 % per dry weight with a saponification value of 178.00 mg KOH/g [15].…”
Section: Extraction Composition and Properties Of Castor Oilmentioning
confidence: 99%
“…For instance, cold-pressed castor oils have low acid value, low iodine value and a slightly higher saponification value than solvent-extracted oil [1]. It has further been observed that castor seeds from different climatic conditions produce castor oils of different composition and physical-chemical properties [14,15,17]. Malaysian castor seeds for instance, contain total lipids (castor oil) reaching up to 43.3 % per dry weight and a saponification value of 182.96 mg KOH/g [14] while for the Nigerian castor seeds, the total lipids (castor oil) is 48 % per dry weight with a saponification value of 178.00 mg KOH/g [15].…”
Section: Extraction Composition and Properties Of Castor Oilmentioning
confidence: 99%
“…The importance of sodium formate in the proposed procedure should be highlighted; a series of its cluster ions generated in ESI served as internal lock mass calibrants; sodium ions present in the solution favoured the formation of sodium adducts in ESI, and the ion [Na(NaCOOH) 3 ] + presenting m/z 226.9515 was applied as an internal standard during quantification (IS). According to the previous reports [1,3,6,11] and based on the determination of FAMEs in cosmetic castor oils carried out in this work by GC-FID, the following fatty acids were considered in the method development: ricinoleic, oleic, linoleic, linolenic, behenic, arachidic, stearic and palmitic. The m/z values selected for the acquisition of analytical signals for individual FAMEs and for IS are listed in materials and methods; selectivity was ensured using the high-resolution mass spectrometer and by applying m/z width AE0.005 during signal acquisition.…”
Section: Set-up Of Fia-esi-qtofms Proceduresmentioning
confidence: 99%
“…Different plants are currently in use as a source of vegetable oils for cosmetic applications; among them, oil extracted from castor bean ( Ricinus communis ) presents interesting physicochemical properties . The main ingredient of castor bean triacylglycerides is ricinoleic acid (12‐hydroxy‐9‐ cis ‐octadecenoic acid, C18:1,OH), which accounts for up to 95% of total fatty acids and confers to this oil higher polarity as compared to other fats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secara teoritis, minyak jarak kepyar memiliki tingkat bilangan iod pada kisaran 82-90 g iod/100 g minyak dan bilangan asam sebesar 2-3 mg KOH/g minyak (Ogunfeyitimi et al 2012). Karakteristik minyak jarak kepyar sangat bergantung pada lokasi geografis dan teknik pemeliharaan tanaman selama penanaman (Omari et al 2015). Hasil pengamatan kondisi reaksi vulkanisasi dan pengujian visualisasi fisik faktis cokelat dirangkum pada Tabel 1.…”
Section: Hasil Dan Pembahasanunclassified